The Impact of Genius Magazine on Students’ English Reading Skills - Rizki Amalyasari, Maya; Putri Annur, Maulidina (Linguapedia, 2025)
Narrative text is one of the texts in reading competency based on the school-based Curriculum. In teaching narrative text, teachers need media to make the teaching and learning process go well. One of the suitable teaching media is a module.  This study specifically explored the implementation of Genius Magazine in teaching narrative text. This research aimed in investigating deeply research on how students’ opinions or perceptions were related to the implementation of Genius Magazine, its effectiveness and practicality in teaching narrative text. The researcher used descriptive qualitative method with two research instruments used, they were observation paper and interview guide. The subjects selected in this study were 9th grade students with English teacher who implemented Genius Magazine in English learning in the classroom. The result of this study showed that students welcomed and agreed with the implementation of this magazine as a media to learn narrative text since it presented narrative text equipped with interesting and colorful illustration. The implementation of Genius Magazine was very effective and practical, students were very enthusiastic, the classroom atmosphere was more lively, students were more active in asking and answering teacher questions, interacting with friends or teachers, and their grades also significantly increased.